Chiral aziridine ring opening: facile synthesis of (R)-mexiletine and (R)-phenoxybenzamine hydrochloride. Issue 38 (16th September 2015) - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, M.
Graphical abstract: Abstract: A simple and efficient synthesis of chiral drugs ( R )-mexiletine1, an anti-arrhythmic drug and ( R )-phenoxybenzamine hydrochloride2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds1 and2 were obtained in overall yields of 34% and 10.5%, respectively.